2011
DOI: 10.1007/s12070-010-0064-y
|View full text |Cite
|
Sign up to set email alerts
|

Skin Prick Testing and Immunotherapy in Nasobronchial Allergy: Our Experience

Abstract: In the present study of 331 patients suffering from signs/symptoms of nasal allergy, 9 nasal polyps, allergic conjunctivitis and allergic asthma, who were referred by clinician, were taken up for diagnosis of allergy with skin prick test (Ten et al. Mayo Clin Proc 70(8):783-784, 1995) and subjective improvement of patients by immunotherapy. Out of 331 patients tested 321 patients showed significant positive results and rest of them tested negative for allergy. High incidences of positive results were noted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…The highest rates of HDM sensitization were reported in Singapore (70 to >90%), followed by Taiwan (85-90%) and South India (89.7%). 5,16,24,25 The lowest sensitization rates were described in North India (7.8%), Vietnam (9-23%) and Philippines (33-47%). 15,22,27 Atopic Asians were mostly sensitized to the Dermatophagoides house dust mite species, with a slightly lower percentage sensitized to Blomia Tropicalis.…”
Section: Aeroallergen Sensitization Patterns In Asian Countriesmentioning
confidence: 99%
See 2 more Smart Citations
“…The highest rates of HDM sensitization were reported in Singapore (70 to >90%), followed by Taiwan (85-90%) and South India (89.7%). 5,16,24,25 The lowest sensitization rates were described in North India (7.8%), Vietnam (9-23%) and Philippines (33-47%). 15,22,27 Atopic Asians were mostly sensitized to the Dermatophagoides house dust mite species, with a slightly lower percentage sensitized to Blomia Tropicalis.…”
Section: Aeroallergen Sensitization Patterns In Asian Countriesmentioning
confidence: 99%
“…Aeroallergen sensitization patterns in atopic individuals in various Asian countries, namely China, Hong Kong, India, Japan, Korea, Malaysia, Philippines, Singapore, Taiwan, Thailand and Vietnam are shown in the Table 1 and Figure 1. 5,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] No published data from Myanmar, Laos and Cambodia were available. Studies involving aeroallergen distribution alone without human sensitization, and those involving sensitization without associated atopy were not included.…”
Section: Aeroallergen Sensitization Patterns In Asian Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Another study from Southern India in patients with nasobronchial allergy showed a high prevalence of mite allergy (73.7%) and pollen allergy (75.8%). 24 The reason for this difference from the same geographical area is probably because of seasonal and annual fluctuations in allergens. Heterogeneity in allergen extract composition can lead to the different patterns of sensitization observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The highest sensitivity was found towards Parthenium hysterophorus (30.21%), Prosopis juliflora (25.67%), Eucalyptus spp. (20.54%), Brassica nigra (15.40%), followed by a lesser number of people sensitive towards Chenopodium album, Cocos nucifera, and Acacia arabica [8]. More than 80% out of 331 patients had naso-polips.…”
Section: In Southern Regionmentioning
confidence: 98%